2012
DOI: 10.1002/jsfa.5545
|View full text |Cite
|
Sign up to set email alerts
|

Effect of soy flour addition and heat‐processing method on nutritional quality and consumer acceptability of cassava complementary porridges

Abstract: BACKGROUND: Nutritional quality of cassava complementary porridge improved through

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 40 publications
(62 reference statements)
2
32
0
Order By: Relevance
“…The observation that taste and aroma were best predictors of porridge acceptability in the current study, corroborated the findings of Amegovu et al (2014). The findings that extruded products were more liked by consumers contrasted studies by Muoki et al (2012) and Ndibalema (2011) who observed that, extruded products were less liked by consumers partly due to the development of volatile flavour compounds during extrusion which were not accustomed to the consumers.…”
Section: Consumer Evaluation Studysupporting
confidence: 89%
“…The observation that taste and aroma were best predictors of porridge acceptability in the current study, corroborated the findings of Amegovu et al (2014). The findings that extruded products were more liked by consumers contrasted studies by Muoki et al (2012) and Ndibalema (2011) who observed that, extruded products were less liked by consumers partly due to the development of volatile flavour compounds during extrusion which were not accustomed to the consumers.…”
Section: Consumer Evaluation Studysupporting
confidence: 89%
“…Twenty women from nine sub-Saharan Africa countries (Congo, Gabon, Ghana, Kenya, Malawi, Nigeria, Rwanda, Zambia, and Zimbabwe), resident in Palmerston North (PN), New Zealand (NZ), who had experience of feeding a child with cereal-based porridge prepared at the household level and responded to the advertisement to participate in the consumer sensory evaluation were invited to the Institute of Food, Nutrition and Human Health, Massey University, PN, NZ. Mothers have been employed to assess the consumer acceptance of cassava–soyabean complementary foods (29). The sensory attributes evaluated for the selected complementary foods included overall acceptability, colour, smell, texture, and taste using a 9-point hedonic scale with 1 as least acceptable/dislike extremely and 9 as highly acceptable/like extremely.…”
Section: Methodsmentioning
confidence: 99%
“…Cassava (Manihot esculenta Crantz), which is a staple food in many of these countries is a rich source of carbohydrates but a poor source of protein [1]. One way of improving the protein content of cassava products is to add protein-rich material such as soybean flour [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have carried out on protein fortification of cassava products using soy flour, e.g. cassava flour [2] and garri [3,9,10]. Muoki et al, 2012 [2] reported that a complementary porridge made through extrusion of a mixture of cassava flour and soy flour had acceptable sensory properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation